Adhesive sheet, repeatedly bent laminated member and repeatedly bent device

The adhesive sheet with tailored physical properties addresses the issue of peeling and light leakage in repeatedly bent displays by ensuring strong bonding and minimal stress at the interface, thereby maintaining visibility.

JP7671880B2Active Publication Date: 2025-05-02LINTEC CORP
View PDF 23 Cites 0 Cited by

Patent Information

Application Number
JP2024009489
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-01-25
Publication Date
2025-05-02
Estimated Expiration
2039-09-18

AI Technical Summary

Technical Problem

Conventional adhesive sheets used in repeatedly bent displays experience peeling at the interface between the adhesive layer and the adherend in the bent portion, leading to light leakage and reduced visibility.

Method used

An adhesive sheet with a pressure-sensitive adhesive layer having specific physical properties, including a storage elastic modulus of 0.01MPa to 0.2MPa at -20°C and an absolute value of the photoelastic coefficient of 9.9×10^-10 m²/N or less at 23°C, is used to bond flexible members in repeatedly bent devices.

Benefits of technology

The adhesive sheet effectively prevents peeling at the interface, suppresses light leakage, and maintains visibility even after repeated bending.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671880000003
    Figure 0007671880000003
  • Figure 0007671880000004
    Figure 0007671880000004
  • Figure 0007671880000005
    Figure 0007671880000005
Patent Text Reader

Abstract

To provide: an adhesive sheet that is difficult to generate peeling in an interface between an adhesive layer and an adherend in a bending part and can suppress light leakage and recognizability deterioration due to bending; a repeatedly bendable laminated member; and a repeatedly bendable device.SOLUTION: A repeatedly bendable laminate member 2 comprises: one flexible member 21 and another flexible member 22 that constitute a device that is repeatedly bendable; and an adhesive layer 11 that bonds the one flexible member 21 and the other flexible member 22 to each other. In the repeatedly bendable laminated member 2, the storage elastic modulus G'(-20) of the adhesive constituting the adhesive layer 11 at -20°C and a measurement frequency of 1 Hz is 0.01 MPa or more and 0.20 MPa or less, and the adhesive constituting the adhesive agent layer 11 is an adhesive formed by crosslinking an adhesive composition containing a (meth)acrylic acid ester polymer (A) and a crosslinking agent (B), and the methacrylic acid ester polymer (A) contains an aromatic ring-containing monomer in an amount of 0.1 mass% or more and 9 mass% or less as a monomer unit constituting the polymer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive sheet for a device that is repeatedly bent, as well as a repeatedly bent laminated member and a repeatedly bent device. [Background technology]

[0002] In recent years, bendable displays have been proposed as displays for electronic devices, which are a type of device. In addition to displays that are curved only once, repeatedly bent displays that are repeatedly bent (folded) have also been proposed.

[0003] In the above-mentioned repeatedly bent display, it is considered that one bendable member (flexible member) constituting the said bent display and another bendable member are bonded with an adhesive layer of an adhesive sheet. However, when a conventional adhesive sheet is used in a repeatedly bent display, a problem occurs in that peeling occurs at the interface between the adhesive layer and the adherend at the bent portion.

[0004] Patent Document 1 discloses a pressure-sensitive adhesive intended to suppress the occurrence of peeling during repeated bending. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-108555 A Summary of the Invention [Problem to be solved by the invention]

[0006] On the other hand, in the repeatedly bent display as described above, light leakage may occur around the bent portion during or after bending, and visibility may decrease. The adhesive described in Patent Document 1 cannot sufficiently solve the problems of light leakage and decreased visibility.

[0007] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide an adhesive sheet, a repeatedly bent laminated member, and a repeatedly bent device that are less likely to cause peeling at the interface between the adhesive layer and the adherend in bent sections, and that suppress light leakage and reduced visibility due to bending. [Means for solving the problem]

[0008] In order to achieve the above object, first, the present invention provides a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer for bonding one flexible member and another flexible member that constitute a device that is repeatedly bent, the pressure-sensitive adhesive layer having a storage modulus G'(-20) at -20°C of 0.01 MPa or more and 0.2 MPa or less, and the pressure-sensitive adhesive that constitutes the pressure-sensitive adhesive layer has an absolute value of a photoelastic coefficient at 23°C and a measurement wavelength of 400 nm of 9.9 x 10 -10 m 2 / N or less (Invention 1).

[0009] In the above invention (Invention 1), since the adhesive constituting the adhesive layer has the above physical properties, when a laminate formed by bonding one flexible member to another flexible member with the adhesive layer is repeatedly bent or left in a bent state for a long period of time, peeling is unlikely to occur at the interface between the adhesive layer and the adherend at the bent portion, and light leakage and reduced visibility due to (after) bending are suppressed.

[0010] In the above invention (Invention 1), the absolute value of the photoelastic coefficient of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer at 23° C. and a measurement wavelength of 500 nm is 9.9×10 -10 m 2 It is preferable that the ratio is equal to or less than 1 / N (Invention 2).

[0011] In the above inventions (Inventions 1 and 2), the absolute value of the photoelastic coefficient of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer at 23° C. and a measurement wavelength of 600 nm is 9.9×10 -10 m 2It is preferable that the ratio is equal to or less than 1 / N (Invention 3).

[0012] In the above inventions (Inventions 1 to 3), the storage modulus G'(85) at 85°C of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is preferably 0.005 MPa or more and 0.2 MPa or less (Invention 4).

[0013] In the above inventions (Inventions 1 to 4), the storage modulus G'(25) at 25° C. of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is preferably 0.01 MPa or more and 0.2 MPa or less (Invention 5).

[0014] In the above inventions (Inventions 1 to 5), the gel fraction of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is preferably 30% or more and 95% or less (Invention 6).

[0015] In the above inventions (Inventions 1 to 6), the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is preferably an acrylic pressure-sensitive adhesive (Invention 7).

[0016] In the above inventions (Inventions 1 to 7), it is preferable that the adhesive sheet has two release sheets, and the adhesive layer is sandwiched between the release sheets so as to be in contact with the release surfaces of the two release sheets (Invention 8).

[0017] Secondly, the present invention provides a repeatedly bent laminated member (Invention 9), which comprises one flexible member and another flexible member constituting a device that is repeatedly bent, and an adhesive layer that bonds the one flexible member and the other flexible member to each other, wherein the adhesive layer is made of the adhesive layer of the adhesive sheet (Inventions 1 to 8).

[0018] Thirdly, the present invention provides a repeatedly flexed device (Invention 10), comprising the repeatedly flexed laminated member (Invention 9). Effect of the Invention

[0019] The pressure-sensitive adhesive sheet, repeatedly bent laminated member, and repeatedly bent device according to the present invention are less susceptible to peeling at the interface between the pressure-sensitive adhesive layer and the adherend in the bent portion, and light leakage and reduced visibility due to bending are suppressed. [Brief description of the drawings]

[0020] [Figure 1] 1 is a cross-sectional view of a pressure-sensitive adhesive sheet according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of a repeatedly bent laminated member according to one embodiment of the present invention. [Diagram 3] 1 is a cross-sectional view of a repeated bending device according to an embodiment of the present invention. [Figure 4] FIG. 1 is an explanatory diagram (side view) for explaining a static bending test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, an embodiment of the present invention will be described. [Adhesive sheet] The pressure-sensitive adhesive sheet according to one embodiment of the present invention has a pressure-sensitive adhesive layer for bonding one flexible member and another flexible member that constitute a repeatedly flexing device, and is preferably formed by laminating a release sheet on one or both sides of the pressure-sensitive adhesive layer. The repeatedly flexing device and the flexible member will be described later.

[0022] The pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a storage modulus G'(-20) at -20°C of 0.01 MPa or more and 0.2 MPa or less, and the absolute value of the photoelastic coefficient of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer at 23°C and a measurement wavelength of 400 nm is 9.9 x 10 -10 m 2 / N or less. The storage modulus and photoelastic coefficient in this specification are measured by the methods shown in the test examples described later.

[0023] Since the adhesive constituting the adhesive layer in this embodiment has the above physical properties, when a laminate formed by bonding one flexible member to another flexible member with the adhesive layer is repeatedly bent or left in a bent state for a long period of time, peeling is unlikely to occur at the interface between the adhesive layer and the adherend at the bent portion, and light leakage due to bending (after bending) and reduced visibility are suppressed. In particular, when the storage modulus G'(-20) is 0.2 MPa or less, the strain, i.e., stress (which is particularly large at low temperatures), generated by repeated bending can be kept small, and therefore peeling is unlikely to occur at the interface between the adhesive layer and the adherend at the bent portion. In particular, when the photoelastic coefficient is 9.9×10 -10 m 2 When the refractive index is 1.0 or less, the occurrence of birefringence due to residual stress caused by bending can be suppressed, and light leakage and reduced visibility due to bending can be suppressed.

[0024] From the viewpoints of the above-mentioned peel resistance, light leakage resistance, and visibility, particularly from the viewpoint of peel resistance, the storage modulus G'(-20) at -20°C of the adhesive constituting the above-mentioned adhesive layer must be 0.2 MPa or less, preferably 0.15 MPa or less, particularly preferably 0.10 MPa or less, and more preferably 0.08 MPa or less. Also, from the viewpoint of cohesive strength, the storage modulus G'(-20) at -20°C of the adhesive constituting the above-mentioned adhesive layer must be 0.01 MPa or more, preferably 0.03 MPa or more, particularly preferably 0.05 MPa or more, and more preferably 0.07 MPa or more.

[0025] The storage modulus G'(85) at 85°C of the adhesive constituting the adhesive layer is preferably 0.2 MPa or less, more preferably 0.1 MPa or less, particularly preferably 0.05 MPa or less, and even more preferably 0.03 MPa or less. This reduces the force acting on the adherend from the adhesive layer with bending, and a device with excellent peel resistance at high temperatures can be obtained. On the other hand, the storage modulus G'(85) at 85°C is preferably 0.005 MPa or more, more preferably 0.010 MPa or more, and particularly preferably 0.015 MPa or more. This allows the adhesive layer to maintain its cohesive force even at high temperatures without becoming too soft.

[0026] The storage modulus G'(25) at 25°C of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is preferably 0.2 MPa or less, more preferably 0.1 MPa or less, particularly preferably 0.08 MPa or less, and even more preferably 0.05 MPa or less. This makes it easier to exert adhesive properties. On the other hand, the storage modulus G'(25) at 25°C is preferably 0.01 MPa or more, more preferably 0.02 MPa or more, and particularly preferably 0.03 MPa or more. This provides excellent peel resistance in the standard environmental temperature range, as well as good processability such as punching.

[0027] From the viewpoints of the above-mentioned peel resistance, light leakage resistance, and visibility, particularly from the viewpoints of light leakage resistance and visibility, the absolute value of the photoelastic coefficient of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer at 23° C. and a measurement wavelength of 400 nm is 9.9×10 -10 m 2 / N or less, 8.0×10 -10 m 2 / N or less, and 6.0×10 -10 m 2 / N or less, and more preferably 5.0×10 -10 m 2 The lower limit of the absolute value of the photoelastic coefficient is not particularly limited, and is preferably 0m 2However, from the viewpoint of easily obtaining a pressure-sensitive adhesive having a storage modulus G'(-20) at -20°C that satisfies the above-mentioned value, the absolute value of the photoelastic coefficient may be 1.0 × 10 -10 m 2 / N or more, and 2.0×10 -10 m 2 / N or more, and 3.0×10 -10 m 2 / N or more, and more preferably 4.0×10 -10 m 2 It is preferable that the ratio is equal to or larger than / N.

[0028] From the viewpoint of further improving light leakage resistance and visibility, the absolute value of the photoelastic coefficient of the adhesive constituting the above-mentioned adhesive layer at 23° C. and a measurement wavelength of 500 nm is 9.9×10 -10 m 2 / N or less, and 8.0×10 -10 m 2 / N or less, and more preferably 6.0×10 -10 m 2 / N or less, and more preferably 5.0×10 -10 m 2 The lower limit of the absolute value of the photoelastic coefficient is not particularly limited, and is preferably 0m 2 However, from the viewpoint of easily obtaining a pressure-sensitive adhesive having a storage modulus G'(-20) at -20°C that satisfies the above-mentioned value, the absolute value of the photoelastic coefficient may be 1.0 × 10 -10 m 2 / N or more, and 2.0×10 -10 m 2 / N or more, and more preferably 3.0×10 -10 m 2 / N or more, and more preferably 3.5×10 -10 m 2 It is preferable that the ratio is equal to or larger than / N.

[0029] From the viewpoint of improving light leakage resistance and visibility, the absolute value of the photoelastic coefficient of the adhesive constituting the above-mentioned adhesive layer at 23° C. and a measurement wavelength of 600 nm is 9.9×10-10 m 2 / N or less, and 8.0×10 -10 m 2 / N or less, and more preferably 6.0×10 -10 m 2 / N or less, and more preferably 4.0×10 -10 m 2 The lower limit of the absolute value of the photoelastic coefficient is not particularly limited, and is preferably 0m 2 However, from the viewpoint of easily obtaining a pressure-sensitive adhesive having a storage modulus G'(-20) at -20°C that satisfies the above-mentioned value, the absolute value of the photoelastic coefficient may be 0.8 × 10 -10 m 2 / N or more, and 1.5×10 -10 m 2 / N or more, and more preferably 2.0×10 -10 m 2 / N or more, and more preferably 3.0×10 -10 m 2 It is preferable that the ratio is equal to or larger than / N.

[0030] The difference between the maximum and minimum absolute values ​​of the photoelastic coefficient at 23°C, measurement wavelength of 400 nm, measurement wavelength of 500 nm, and measurement wavelength of 600 nm of the adhesive constituting the above adhesive layer is 8 x 10 -10 m 2 / N or less is preferable, and 4×10 -10 m 2 / N or less is preferable, and 2.0×10 -10 m 2 / N or less is particularly preferable, and 1.5×10 -10 m 2 It is more preferable that the ratio is equal to or less than 1 / N. This makes it possible to suppress the influence of differences in the types of illuminants used on the resistance to light leakage and visibility.

[0031] The gel fraction of the adhesive constituting the above-mentioned adhesive layer is preferably 30% or more, more preferably 40% or more, particularly preferably 50% or more, and even more preferably 60% or more. This allows the adhesive to exhibit a suitable cohesive force capable of withstanding repeated bending. As a result, the above-mentioned peel resistance is more excellent. On the other hand, the gel fraction of the adhesive in this embodiment is preferably 95% or less, more preferably 90% or less, particularly preferably 80% or less, even more preferably 75% or less, and most preferably 70% or less. This is presumed to suppress the destruction of the crosslinked structure in the adhesive due to repeated bending, and the visibility is more excellent. The method for measuring the gel fraction in this specification is as shown in the test example described later.

[0032] FIG. 1 shows a specific configuration of one example of the pressure-sensitive adhesive sheet according to this embodiment. 1, an adhesive sheet 1 according to one embodiment is composed of two release sheets 12a, 12b and an adhesive layer 11 sandwiched between the two release sheets 12a, 12b so as to be in contact with the release surfaces of the two release sheets 12a, 12b. In this specification, the release surface of a release sheet refers to a surface of the release sheet that has releasability, and includes both a surface that has been subjected to a release treatment and a surface that exhibits releasability even without being subjected to a release treatment.

[0033] 1. Components 1-1. Adhesive layer The adhesive layer 11 is made of an adhesive having the above-mentioned physical properties. The type of adhesive constituting the adhesive layer 11 is not particularly limited as long as the above-mentioned physical properties (particularly the storage modulus G'(-20) at -20°C and the photoelastic coefficient at 23°C and a measurement wavelength of 400 nm) are satisfied, and may be, for example, any of an acrylic adhesive, a polyester adhesive, a polyurethane adhesive, a rubber adhesive, a silicone adhesive, etc. In addition, the adhesive may be any of an emulsion type, a solvent type, or a solventless type, and may be any of a crosslinked type or a non-crosslinked type. Among them, an acrylic adhesive that easily satisfies the above-mentioned physical properties and has excellent adhesive properties and optical properties is preferred, and a solvent-type acrylic adhesive is particularly preferred.

[0034] Specifically, the adhesive in this embodiment is preferably an adhesive obtained by crosslinking an adhesive composition (hereinafter sometimes referred to as "adhesive composition P") containing a (meth)acrylic acid ester polymer (A) and a crosslinking agent (B). Such an adhesive can satisfy the above-mentioned physical properties and is likely to provide good adhesive strength. In this specification, (meth)acrylic acid means both acrylic acid and methacrylic acid. The same applies to other similar terms. In addition, "polymer" is also intended to include the concept of "copolymer."

[0035] (1) Components of adhesive composition P (1-1) (Meth)acrylic acid ester polymer (A) The (meth)acrylic acid ester polymer (A) preferably contains, as a monomer unit constituting the polymer, an alkyl (meth)acrylic acid ester for exhibiting good adhesion and a monomer having a reactive functional group (monomer containing a reactive functional group) which serves as a crosslinking point. Here, a normal alkyl (meth)acrylic acid ester exhibits negative birefringence, and the resulting polymer has birefringence, but by incorporating a monomer exhibiting positive birefringence into the polymer, the birefringence can be eliminated by canceling out the positive and negative. This allows the absolute value of the photoelastic coefficient of the resulting adhesive to be kept small, making it easier to meet the above-mentioned photoelastic coefficient. In addition, the alkyl (meth)acrylic acid ester tends to reduce the storage modulus of the resulting polymer, while the monomer exhibiting positive birefringence (especially the aromatic ring-containing monomer described later) tends to increase the storage modulus of the resulting polymer, and by incorporating both into the polymer, the physical properties related to the storage modulus G' described above are easier to meet. Therefore, it is more preferable that the (meth)acrylic acid ester polymer (A) contains, as monomer units constituting the polymer, an alkyl (meth)acrylic acid ester, a monomer exhibiting positive birefringence, and a monomer containing a reactive functional group.

[0036] The (meth)acrylic acid alkyl ester preferably includes a (meth)acrylic acid alkyl ester in which the carbon number of the alkyl group is 1 to 20. The alkyl group is preferably linear or branched.

[0037] Examples of (meth)acrylic acid alkyl esters having an alkyl group with 1 to 20 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, and stearyl (meth)acrylate. Among these, from the viewpoint of the above-mentioned storage modulus G' and photoelastic coefficient, (meth)acrylic acid esters having an alkyl group with 1 to 8 carbon atoms are preferred, and (meth)acrylic acid esters having an alkyl group with 4 to 8 carbon atoms are particularly preferred. Specifically, n-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate are preferred, and n-butyl acrylate and 2-ethylhexyl acrylate are particularly preferred. These may be used alone or in combination of two or more.

[0038] The (meth)acrylic acid ester polymer (A) preferably contains 50% by mass or more, more preferably 70% by mass or more, particularly preferably 80% by mass or more, and even more preferably 90% by mass or more of the (meth)acrylic acid alkyl ester having 1 to 20 carbon atoms in the alkyl group as a monomer unit constituting the polymer. The (meth)acrylic acid alkyl ester is preferably contained in an amount of 99% by mass or less, more preferably 98% by mass or less, particularly preferably 97% by mass or less, and even more preferably 96% by mass or less. When the (meth)acrylic acid alkyl ester having 1 to 20 carbon atoms in the alkyl group is contained in the above amount, it is possible to impart suitable adhesion to the (meth)acrylic acid ester polymer (A), and the storage elastic modulus G' and photoelastic coefficient described above are easily satisfied.

[0039] As the monomer exhibiting positive birefringence, a monomer having a cyclic structure is preferably mentioned, and in particular, a monomer having an aromatic ring (aromatic ring-containing monomer) is preferably mentioned. As the aromatic ring, a benzene ring, a naphthalene ring, an anthracene ring, a biphenyl ring, a fluorene ring, etc. are mentioned, and among them, a benzene ring is preferable from the viewpoint of positive birefringence.

[0040] Examples of aromatic ring-containing monomers include phenyl (meth)acrylate, 2-phenylethyl (meth)acrylate, benzyl (meth)acrylate, naphthyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, phenoxybutyl (meth)acrylate, ethoxylated o-phenylphenol acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, biphenyl di(meth)acrylate, and pentafluorobenzyl (meth)acrylate. Among these, from the viewpoint of positive birefringence, 2-phenoxyethyl (meth)acrylate or phenoxypolyethylene glycol (meth)acrylate is preferred, particularly 2-phenoxyethyl (meth)acrylate, and further 2-phenoxyethyl acrylate is preferred. These may be used alone or in combination of two or more.

[0041] The (meth)acrylic acid ester copolymer (A) preferably contains 0.1% by mass or more of an aromatic ring-containing monomer as a monomer unit constituting the polymer, more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and even more preferably 2% by mass or more. In addition, it is preferable to contain 30% by mass or less of an aromatic ring-containing monomer, more preferably 20% by mass or less, particularly preferably 15% by mass or less, and even more preferably 9% by mass or less. By the content of the aromatic ring-containing monomer being within the above range, the negative birefringence of the (meth)acrylic acid alkyl ester can be canceled, the birefringence can be more effectively eliminated, and the above-mentioned photoelastic coefficient is more easily satisfied. In addition, the adhesiveness is well maintained.

[0042] The (meth)acrylic acid ester polymer (A) contains a reactive functional group-containing monomer as a monomer unit constituting the polymer, and reacts with the crosslinking agent (B) described later via the reactive functional group derived from the reactive functional group-containing monomer, thereby forming a crosslinked structure (three-dimensional network structure), and a pressure-sensitive adhesive having a desired cohesive strength is obtained. The pressure-sensitive adhesive is likely to satisfy the physical properties related to the storage modulus G' and the photoelastic coefficient (and gel fraction) described above.

[0043] The reactive functional group-containing monomer contained in the (meth)acrylic acid ester polymer (A) as a monomer unit constituting the polymer is preferably a monomer having a hydroxyl group in the molecule (hydroxyl group-containing monomer), a monomer having a carboxyl group in the molecule (carboxyl group-containing monomer), a monomer having an amino group in the molecule (amino group-containing monomer), etc. These reactive functional group-containing monomers may be used alone or in combination of two or more kinds.

[0044] Among the reactive functional group-containing monomers, hydroxyl group-containing monomers or carboxyl group-containing monomers are preferred, and hydroxyl group-containing monomers are particularly preferred.Hydroxyl group-containing monomers are easy to satisfy the physical properties related to the storage modulus G' described above.That is, if the hydroxyl group-containing monomer is used, the storage modulus G' at low temperature can be particularly reduced, and the storage modulus G' of the pressure-sensitive adhesive obtained can be easily fine-tuned.

[0045] Examples of the hydroxyl group-containing monomer include (meth)acrylic acid hydroxyalkyl esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among the above, from the viewpoint of ease of satisfying the physical property related to the storage elastic modulus G' described above, (meth)acrylic acid hydroxyalkyl esters having a hydroxyalkyl group having 1 to 4 carbon atoms are preferred. Specifically, for example, 2-hydroxyethyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and the like are preferred, and in particular, 2-hydroxyethyl acrylate or 4-hydroxybutyl acrylate are preferred. These may be used alone or in combination of two or more.

[0046] Examples of the carboxyl group-containing monomer include ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, itaconic acid, and citraconic acid. Among them, acrylic acid is preferred from the viewpoint of the adhesive strength of the (meth)acrylic acid ester polymer (A) obtained. These may be used alone or in combination of two or more kinds.

[0047] In addition, 2-hydroxyethyl acrylate, 4-hydroxybutyl acrylate, and acrylic acid exhibit positive birefringence, and therefore, together with the above-mentioned monomer exhibiting positive birefringence (monomer containing an aromatic ring), can contribute to canceling the negative birefringence of the (meth)acrylic acid alkyl ester.

[0048] The (meth)acrylic acid ester polymer (A) preferably contains 0.1% by mass or more of reactive functional group-containing monomer as a monomer unit constituting the polymer, particularly preferably 0.4% by mass or more, and more preferably 0.8% by mass or more. The (meth)acrylic acid ester polymer (A) preferably contains 18% by mass or less of reactive functional group-containing monomer as a monomer unit constituting the polymer, particularly preferably 9% by mass or less, and more preferably 3% by mass or less. When the (meth)acrylic acid ester polymer (A) contains the reactive functional group-containing monomer as a monomer unit in the above amount, the cohesive force of the resulting pressure-sensitive adhesive becomes appropriate due to the crosslinking reaction with the crosslinking agent (B), and the physical properties related to the storage modulus G' (and gel fraction), particularly the storage modulus G' (-20) at -20 ° C., are easily satisfied.

[0049] It is also preferred that the (meth)acrylic acid ester polymer (A) does not contain a carboxyl group-containing monomer as a monomer unit constituting the polymer. Since a carboxyl group is an acid component, by not containing a carboxyl group-containing monomer, even if the target to which the pressure-sensitive adhesive is applied includes a transparent conductive film such as tin-doped indium oxide (ITO), a metal film, a metal mesh, etc., which may be affected by acid, the absence of a carboxyl group-containing monomer can suppress such defects (corrosion, change in resistance, etc.) caused by acid.

[0050] Here, "free of carboxyl group-containing monomer" means that the carboxyl group-containing monomer is not substantially contained, and in addition to not containing any carboxyl group-containing monomer at all, the carboxyl group-containing monomer may be contained to an extent that the carboxyl group does not cause corrosion of the transparent conductive film, metal wiring, etc. Specifically, the (meth)acrylic acid ester polymer (A) may contain the carboxyl group-containing monomer as a monomer unit in an amount of 0.1% by mass or less, preferably 0.01% by mass or less, and more preferably 0.001% by mass or less.

[0051] The (meth)acrylic acid ester polymer (A) may contain other monomers as monomer units constituting the polymer, if desired. As the other monomers, monomers not containing reactive functional groups are preferred so as not to inhibit the above-mentioned action of the reactive functional group-containing monomer. Examples of such monomers include non-reactive nitrogen atom-containing monomers such as N-acryloylmorpholine and N-vinyl-2-pyrrolidone, (meth)acrylic acid alkoxyalkyl esters such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, vinyl acetate, and styrene. These may be used alone or in combination of two or more.

[0052] The polymerization mode of the (meth)acrylic acid ester polymer (A) may be a random copolymer or a block copolymer.

[0053] The weight average molecular weight of the (meth)acrylic acid ester polymer (A) is preferably 600,000 or more, more preferably 800,000 or more, particularly preferably 1,000,000 or more, and even more preferably 1,200,000 or more. The weight average molecular weight of the (meth)acrylic acid ester polymer (A) is preferably 2,500,000 or less, more preferably 2,000,000 or less, particularly preferably 1,700,000 or less, and even more preferably 1,400,000 or less. When the weight average molecular weight of the (meth)acrylic acid ester polymer (A) is within the above range, it is easy to satisfy the physical properties (and gel fraction) related to the storage modulus G' described above, particularly the storage modulus G'(25) at 25 ° C. and the storage modulus G'(85) at 85 ° C. The weight average molecular weight in this specification is a value measured by gel permeation chromatography (GPC) in terms of standard polystyrene.

[0054] In the pressure-sensitive adhesive composition P, the (meth)acrylic acid ester polymer (A) may be used alone or in combination of two or more kinds.

[0055] (1-2) Crosslinking agent (B) The crosslinking agent (B) crosslinks the (meth)acrylic acid ester polymer (A) and forms a three-dimensional network structure when the pressure-sensitive adhesive composition P containing the crosslinking agent (B) is heated or the like, which is a trigger. This improves the cohesive strength of the resulting pressure-sensitive adhesive, and makes it easier to satisfy the above-mentioned physical properties related to the storage modulus G' and the gel fraction.

[0056] The crosslinking agent (B) may be any one that reacts with the reactive group of the (meth)acrylic acid ester polymer (A), and examples thereof include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, amine-based crosslinking agents, melamine-based crosslinking agents, aziridine-based crosslinking agents, hydrazine-based crosslinking agents, aldehyde-based crosslinking agents, oxazoline-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, and ammonium salt-based crosslinking agents. Among the above, it is preferable to use an isocyanate-based crosslinking agent that has excellent reactivity with a reactive functional group-containing monomer. The crosslinking agent (B) may be used alone or in combination of two or more.

[0057] The isocyanate-based crosslinking agent contains at least a polyisocyanate compound. Examples of the polyisocyanate compound include aromatic polyisocyanates such as tolylene diisocyanate, diphenylmethane diisocyanate, and xylylene diisocyanate, aliphatic polyisocyanates such as hexamethylene diisocyanate, alicyclic polyisocyanates such as isophorone diisocyanate and hydrogenated diphenylmethane diisocyanate, and their biuret and isocyanurate forms, as well as adducts which are reactants with low-molecular active hydrogen-containing compounds such as ethylene glycol, propylene glycol, neopentyl glycol, trimethylolpropane, and castor oil. Among these, trimethylolpropane-modified aromatic polyisocyanates, particularly trimethylolpropane-modified tolylene diisocyanate or trimethylolpropane-modified xylylene diisocyanate, are preferred from the viewpoint of reactivity with hydroxyl groups.

[0058] The content of the crosslinking agent (B) in the adhesive composition P is preferably 0.01 parts by mass or more, more preferably 0.06 parts by mass or more, and even more preferably 0.12 parts by mass or more, based on 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is preferably 5 parts by mass or less, more preferably 2 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.4 parts by mass or less. When the content of the crosslinking agent (B) is within the above range, the physical properties related to the storage modulus G' and the gel fraction described above are easily satisfied.

[0059] (1-3) Various additives If desired, various additives that are commonly used in acrylic adhesives, such as a silane coupling agent, an ultraviolet absorber, an antistatic agent, a tackifier, an antioxidant, a light stabilizer, a softener, a filler, a refractive index adjuster, etc., can be added to the adhesive composition P. Note that polymerization solvents and dilution solvents described below are not included in the additives that constitute the adhesive composition P.

[0060] The pressure-sensitive adhesive composition P preferably contains the above-mentioned silane coupling agent, which improves the adhesion of the resulting pressure-sensitive adhesive layer to the flexible member that is the adherend, and provides more preferable adhesive strength.

[0061] The silane coupling agent is preferably an organosilicon compound having at least one alkoxysilyl group in the molecule, which has good compatibility with the (meth)acrylic acid ester polymer (A) and has optical transparency.

[0062] Examples of such silane coupling agents include polymerizable unsaturated group-containing silicon compounds such as vinyltrimethoxysilane, vinyltriethoxysilane, and methacryloxypropyltrimethoxysilane; epoxy structure-containing silicon compounds such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, and 3-mercaptopropyldimethoxymethylsilane; Examples of the silane include capryl group-containing silicon compounds, amino group-containing silicon compounds such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, and 3-isocyanatepropyltriethoxysilane, or condensates of at least one of these with alkyl group-containing silicon compounds such as methyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, and ethyltrimethoxysilane. These may be used alone or in combination of two or more.

[0063] The content of the silane coupling agent in the adhesive composition P is preferably 0.01 parts by mass or more, particularly preferably 0.05 parts by mass or more, and even more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the (meth)acrylic acid ester polymer (A). The content is preferably 1 part by mass or less, particularly preferably 0.5 parts by mass or less, and even more preferably 0.3 parts by mass or less. When the content of the silane coupling agent is within the above range, the adhesive layer obtained has improved adhesion to the flexible member, which is the adherend, and has greater adhesive strength.

[0064] (2) Preparation of adhesive composition P The adhesive composition P can be produced by producing a (meth)acrylic acid ester polymer (A), mixing the resulting (meth)acrylic acid ester polymer (A) with a crosslinking agent (B), and adding additives as desired.

[0065] The (meth)acrylic acid ester polymer (A) can be produced by polymerizing a mixture of monomers constituting the polymer by a normal radical polymerization method. The polymerization of the (meth)acrylic acid ester polymer (A) is preferably carried out by a solution polymerization method using a polymerization initiator as desired. By polymerizing the (meth)acrylic acid ester polymer (A) by a solution polymerization method, it becomes easy to increase the molecular weight of the obtained polymer and adjust the molecular weight distribution, and further it becomes possible to reduce the generation of low molecular weight substances. Therefore, even if the gel fraction is relatively small and the degree of crosslinking is relaxed, the pressure-sensitive adhesive is unlikely to become biased due to repeated bending, and a pressure-sensitive adhesive with excellent peel resistance is easily obtained.

[0066] Examples of the polymerization solvent used in the solution polymerization method include ethyl acetate, n-butyl acetate, isobutyl acetate, toluene, acetone, hexane, and methyl ethyl ketone, and two or more of these may be used in combination.

[0067] Examples of the polymerization initiator include azo compounds and organic peroxides, and two or more of them may be used in combination. Examples of the azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane 1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].

[0068] Examples of organic peroxides include benzoyl peroxide, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butyl peroxyneodecanoate, t-butyl peroxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.

[0069] In the above polymerization step, the weight average molecular weight of the resulting polymer can be adjusted by adding a chain transfer agent such as 2-mercaptoethanol.

[0070] After the (meth)acrylic acid ester polymer (A) is obtained, the crosslinking agent (B) and, if desired, additives and a dilution solvent are added to the solution of the (meth)acrylic acid ester polymer (A) and mixed thoroughly to obtain a pressure-sensitive adhesive composition P (coating solution) diluted with the solvent.

[0071] In addition, when any of the above components is used in a solid state, or when precipitation occurs when the component is mixed with other components in an undiluted state, the component may be dissolved or diluted in a dilution solvent before being mixed with the other components.

[0072] Examples of the dilution solvent include aliphatic hydrocarbons such as hexane, heptane, and cyclohexane; aromatic hydrocarbons such as toluene and xylene; halogenated hydrocarbons such as methylene chloride and ethylene chloride; alcohols such as methanol, ethanol, propanol, butanol, and 1-methoxy-2-propanol; ketones such as acetone, methyl ethyl ketone, 2-pentanone, isophorone, and cyclohexanone; esters such as ethyl acetate and butyl acetate; and cellosolve-based solvents such as ethyl cellosolve.

[0073] The concentration and viscosity of the coating solution thus prepared are not particularly limited as long as they are within the range that allows coating, and can be appropriately selected according to the situation. For example, the adhesive composition P is diluted so that the concentration becomes 10 to 60 mass %. In addition, when obtaining the coating solution, the addition of a dilution solvent or the like is not a necessary condition, and if the adhesive composition P has a viscosity that allows coating, it is not necessary to add a dilution solvent. In this case, the adhesive composition P becomes a coating solution in which the polymerization solvent of the (meth)acrylic acid ester polymer (A) itself serves as the dilution solvent.

[0074] (3) Manufacture of adhesives The adhesive constituting the adhesive layer 11 in this embodiment is preferably obtained by crosslinking the adhesive composition P. The crosslinking of the adhesive composition P can usually be carried out by a heat treatment. This heat treatment can also serve as a drying treatment for volatilizing a diluting solvent and the like from a coating film of the adhesive composition P applied to a desired object.

[0075] The heating temperature in the heat treatment is preferably 50 to 150° C., and more preferably 70 to 120° C. The heating time is preferably 10 seconds to 10 minutes, and more preferably 50 seconds to 2 minutes.

[0076] After the heat treatment, a curing period of about 1 to 2 weeks may be provided at room temperature (e.g., 23°C, 50% RH) as necessary. If this curing period is required, the adhesive is formed after the curing period has elapsed, and if no curing period is required, the adhesive is formed after the heat treatment is completed.

[0077] By the above heat treatment (and curing), the (meth)acrylic acid ester polymer (A) is sufficiently crosslinked via the crosslinking agent (B) to form a crosslinked structure, thereby obtaining a pressure-sensitive adhesive.

[0078] (4) Thickness of the adhesive layer The thickness (measured according to JIS K7130) of the adhesive layer 11 in the adhesive sheet 1 according to this embodiment is preferably 1 μm or more as a lower limit, more preferably 5 μm or more, particularly preferably 10 μm or more, and even more preferably 15 μm or more. When the thickness of the adhesive layer 11 has the above lower limit, the adhesive layer 11 can easily exert the desired adhesive strength and has better peel resistance.

[0079] The thickness of the adhesive layer 11 is preferably 300 μm or less as an upper limit, more preferably 150 μm or less, particularly preferably 90 μm or less, and from the viewpoint of obtaining a thinner repeatedly bent device, more preferably 40 μm or less. When the upper limit of the thickness of the adhesive layer 11 is as above, the stress generated in the adhesive layer due to repeated bending is prevented from becoming too large, and the peel resistance can be improved. The adhesive layer 11 may be formed as a single layer, or may be formed by laminating multiple layers.

[0080] 1-2.Release sheet Release sheets 12a and 12b protect adhesive layer 11 until adhesive sheet 1 is used, and are peeled off when adhesive sheet 1 (adhesive layer 11) is to be used. In adhesive sheet 1 according to this embodiment, one or both of release sheets 12a and 12b are not necessarily required.

[0081] Examples of the release sheets 12a and 12b include polyethylene films, polypropylene films, polybutene films, polybutadiene films, polymethylpentene films, polyvinyl chloride films, vinyl chloride copolymer films, polyethylene terephthalate films, polyethylene naphthalate films, polybutylene terephthalate films, polyurethane films, ethylene vinyl acetate films, ionomer resin films, ethylene-(meth)acrylic acid copolymer films, ethylene-(meth)acrylic acid ester copolymer films, polystyrene films, polycarbonate films, polyimide films, and fluororesin films. Crosslinked films of these films are also used. Furthermore, laminated films of these films may be used.

[0082] The release surfaces of the release sheets 12a and 12b (particularly the surfaces in contact with the adhesive layer 11) are preferably subjected to a release treatment. Examples of release agents used in the release treatment include alkyd-based, silicone-based, fluorine-based, unsaturated polyester-based, polyolefin-based, and wax-based release agents. It is preferable that one of the release sheets 12a and 12b is a heavy release type release sheet having a large release strength, and the other is a light release type release sheet having a small release strength.

[0083] There is no particular limitation on the thickness of the release sheets 12a and 12b, but it is usually about 20 to 150 μm.

[0084] 2.Physical properties (adhesion) The adhesive strength of the adhesive sheet 1 according to the present embodiment to soda lime glass is preferably 1N / 25mm or more as a lower limit, more preferably 3N / 25mm or more, particularly preferably 5N / 25mm or more, and even more preferably 8N / 25mm or more. When the lower limit of the adhesive strength of the adhesive sheet 1 to soda lime glass is as described above, the peel resistance is more excellent. On the other hand, the upper limit of the adhesive strength is not particularly limited, but reworkability may be required. From this viewpoint, the adhesive strength is preferably 30N / 25mm or less, more preferably 25N / 25mm or less, and particularly preferably 20N / 25mm or less. In this specification, the adhesive strength basically refers to the adhesive strength measured by a 180-degree peeling method in accordance with JIS Z0237:2009, and the specific test method is as shown in the test example described later.

[0085] The adhesive strength of the adhesive sheet 1 according to the present embodiment to polyimide is preferably 1N / 25mm or more as a lower limit, more preferably 3N / 25mm or more, particularly preferably 5N / 25mm or more, and even more preferably 10N / 25mm or more. When the lower limit of the adhesive strength of the adhesive sheet 1 to polyimide is as above, the peel resistance is more excellent even when a polyimide film or the like is used as an adherend. On the other hand, the upper limit of the adhesive strength is not particularly limited, but reworkability may be required. From this viewpoint, the adhesive strength is preferably 30N / 25mm or less, more preferably 25N / 25mm or less, and particularly preferably 20N / 25mm or less.

[0086] 3. Manufacturing of adhesive sheets As an example of manufacturing the adhesive sheet 1, a case where the adhesive composition P is used will be described. A coating solution of the adhesive composition P is applied to the release surface of one of the release sheets 12a (or 12b), and a heat treatment is performed to thermally crosslink the adhesive composition P to form a coating layer, and then the release surface of the other release sheet 12b (or 12a) is superimposed on the coating layer. If a curing period is required, a curing period is left, and if no curing period is required, the coating layer becomes the adhesive layer 11 as is. In this way, the adhesive sheet 1 is obtained. The conditions for the heat treatment and curing are as described above.

[0087] In another manufacturing example of the adhesive sheet 1, a coating solution of the adhesive composition P is applied to the release surface of one release sheet 12a, and a heat treatment is performed to thermally crosslink the adhesive composition P to form a coating layer, thereby obtaining a release sheet 12a with a coating layer. Also, a coating solution of the adhesive composition P is applied to the release surface of the other release sheet 12b, and a heat treatment is performed to thermally crosslink the adhesive composition P to form a coating layer, thereby obtaining a release sheet 12b with a coating layer. Then, the release sheet 12a with a coating layer and the release sheet 12b with a coating layer are bonded together so that both coating layers come into contact with each other. If a curing period is required, a curing period is provided, and if a curing period is not required, the laminated coating layer becomes the adhesive layer 11 as it is. This results in the above-mentioned adhesive sheet 1. According to this manufacturing example, even if the adhesive layer 11 is relatively thick, it is possible to stably manufacture it.

[0088] The coating solution of the pressure-sensitive adhesive composition P can be applied by, for example, bar coating, knife coating, roll coating, blade coating, die coating, gravure coating, or the like.

[0089] [Repeatedly bent laminated member] As shown in FIG. 2, the repeatedly bent laminated member 2 of this embodiment is composed of a first bending member 21 (one bending member), a second bending member 22 (another bending member), and an adhesive layer 11 located between them and bonding the first bending member 21 and the second bending member 22 to each other.

[0090] The pressure-sensitive adhesive layer 11 in the repeatedly folded laminated member 2 is the pressure-sensitive adhesive layer 11 of the pressure-sensitive adhesive sheet 1 described above.

[0091] The repeatedly bent laminate member 2 is a repeatedly bent device itself, or a member constituting a part of a repeatedly bent device. The repeatedly bent device is preferably a display (repeatedly bent display) that can be repeatedly bent (including folding), but is not limited thereto. Examples of such repeatedly bent devices include organic electroluminescence (organic EL) displays, electrophoretic displays (electronic paper), liquid crystal displays using a plastic substrate (film) as a substrate, foldable displays, and the like, and may also be touch panels.

[0092] The first flexible member 21 and the second flexible member 22 are members that can be repeatedly bent (including folded), and examples thereof include cover films, gas barrier films, hard coat films, polarizing films (polarizing plates), polarizers, retardation films (retardation plates), viewing angle compensation films, brightness enhancement films, contrast enhancement films, diffusion films, semi-transmissive reflective films, electrode films, transparent conductive films, metal mesh films, flexible glass, film sensors (touch sensor films), liquid crystal polymer films, light-emitting polymer films, film-like liquid crystal modules, organic EL modules (organic EL films, organic EL elements), electronic paper modules (film-like electronic paper), and TFT (Thin Film Transistor) substrates.

[0093] At least one of the first flexible member 21 and the second flexible member 22 may be a polyimide film or a laminate having a polyimide film on the side of the adhesive layer 11. A polyimide film generally has low adhesion to an adhesive layer, but the adhesive layer 11 in this embodiment provides excellent peel resistance even when the adherend is a polyimide film.

[0094] The Young's modulus of the first bending member 21 and the second bending member 22 is preferably 0.1 to 10 GPa, particularly preferably 0.5 to 7 GPa, and further preferably 1.0 to 5 GPa. When the Young's modulus of the first bending member 21 and the second bending member 22 is within this range, it becomes easy to repeatedly bend each bending member.

[0095] The thickness of each of the first flexible member 21 and the second flexible member 22 is preferably 10 to 3000 μm, particularly preferably 25 to 1000 μm, and further preferably 50 to 500 μm. When the thicknesses of the first flexible member 21 and the second flexible member 22 are within this range, it becomes easy to repeatedly bend each flexible member.

[0096] To manufacture the above-mentioned repeatedly bent laminated member 2, as an example, one release sheet 12a of the adhesive sheet 1 is peeled off and the exposed adhesive layer 11 of the adhesive sheet 1 is attached to one surface of the first flexible member 21.

[0097] Thereafter, the other release sheet 12b is peeled off from the adhesive layer 11 of the adhesive sheet 1, and the exposed adhesive layer 11 of the adhesive sheet 1 is bonded to the second flexible member 22 to obtain the repeatedly bent laminated member 2. As another example, the bonding order of the first flexible member 21 and the second flexible member 22 may be reversed.

[0098] [Repeated bending device] The repeatedly bent device according to this embodiment includes the repeatedly bent laminate member 2, and may be composed of only the repeatedly bent laminate member 2, or may include one or more repeatedly bent laminate members 2 and other flexible members. When one repeatedly bent laminate member 2 and another repeatedly bent laminate member 2 are laminated, or when the repeatedly bent laminate member 2 and another flexible member are laminated, it is preferable to laminate them via the adhesive layer 11 of the adhesive sheet 1 described above.

[0099] In the repeatedly bent device of this embodiment, the adhesive layer is made of the above-mentioned adhesive, so even when the device is repeatedly bent or left in a bent state for a long period of time, peeling is unlikely to occur at the interface between the adhesive layer and the adherend at the bent portion, and light leakage and reduced visibility due to bending are suppressed.

[0100] A repeatedly bending device as an example of this embodiment is shown in Fig. 3. Note that the repeatedly bending device according to the present invention is not limited to this repeatedly bending device.

[0101] 3, the repeatedly bent device 3 according to this embodiment is configured by laminating, from the top, a cover film 31, a first adhesive layer 32, a polarizing film 33, a second adhesive layer 34, a touch sensor film 35, a third adhesive layer 36, an organic EL element 37, a fourth adhesive layer 38, and a TFT substrate 39. The cover film 31, the polarizing film 33, the touch sensor film 35, the organic EL element 37, and the TFT substrate 39 correspond to the flexible member.

[0102] At least one of the first adhesive layer 32, the second adhesive layer 34, the third adhesive layer 36, and the fourth adhesive layer 38 is the adhesive layer 11 of the adhesive sheet 1 described above. It is preferable that two or more of the first adhesive layer 32, the second adhesive layer 34, the third adhesive layer 36, and the fourth adhesive layer 38 are the adhesive layer 11 of the adhesive sheet 1 described above, and it is most preferable that all of the adhesive layers 32, 34, 36, and 38 are the adhesive layer 11 of the adhesive sheet 1.

[0103] Here, for example, when the TFT substrate 39 includes a polyimide film, particularly when the TFT substrate 39 is provided with a polyimide film on the fourth adhesive layer 38 side, it is preferable that at least the fourth adhesive layer 38 is the adhesive layer 11 of the adhesive sheet 1 described above.

[0104] The above-described embodiments are described for the purpose of facilitating understanding of the present invention, and are not described for the purpose of limiting the present invention. Therefore, each element disclosed in the above embodiment is intended to include all design modifications and equivalents that fall within the technical scope of the present invention.

[0105] For example, either one or both of release sheets 12a, 12b in pressure-sensitive adhesive sheet 1 may be omitted, and a desired flexible member may be laminated in place of release sheets 12a and / or 12b. EXAMPLES

[0106] The present invention will be described in more detail below with reference to examples, but the scope of the present invention is not limited to these examples.

[0107] Example 1 1. Preparation of (meth)acrylic acid ester polymer (A) 46 parts by mass of n-butyl acrylate, 50 parts by mass of 2-ethylhexyl acrylate, 1 part by mass of 4-hydroxybutyl acrylate, and 3 parts by mass of 2-phenoxyethyl acrylate were copolymerized by a solution polymerization method to prepare a (meth)acrylic acid ester polymer (A). The molecular weight of this (meth)acrylic acid ester polymer (A) was measured by the method described below, and the weight average molecular weight (Mw) was 1.2 million.

[0108] 2. Preparation of adhesive composition 100 parts by mass (solid content equivalent; the same applies below) of the (meth)acrylic acid ester polymer (A) obtained in step 1 above, 0.14 parts by mass of trimethylolpropane-modified xylylene diisocyanate (XDI; manufactured by Soken Chemical Industries, Ltd., product name "TD-75") as the crosslinking agent (B), and 0.20 parts by mass of 3-glycidoxypropyltrimethoxysilane as the silane coupling agent were mixed, thoroughly stirred, and diluted with methyl ethyl ketone to obtain a coating solution of the adhesive composition.

[0109] 3. Manufacturing of adhesive sheets The obtained adhesive composition coating solution was applied by a knife coater to the release-treated surface of a heavy-release type release sheet (manufactured by Lintec Corporation, product name "SP-PET752150"), one side of which was a polyethylene terephthalate film treated with a silicone-based release agent. The coating layer was then heated at 90°C for 1 minute to form a coating layer.

[0110] Next, the coating layer on the heavy release type release sheet obtained above and a light release type release sheet (manufactured by Lintec Corporation, product name "SP-PET381130"), one side of which is a polyethylene terephthalate film treated with a silicone-based release agent, are attached so that the release-treated surface of the light release type release sheet comes into contact with the coating layer, and the sheet is cured for 7 days under conditions of 23°C and 50% RH to produce an adhesive sheet having an adhesive layer with a thickness of 25 μm, that is, an adhesive sheet having a configuration of heavy release type release sheet / adhesive layer (thickness: 25 μm) / light release type release sheet. The thickness of the adhesive layer is a value measured using a constant pressure thickness gauge (manufactured by Techroc Corporation, product name "PG-02") in accordance with JIS K7130.

[0111] Here, the formulations (solid content equivalent) of the pressure-sensitive adhesive composition when the (meth)acrylic acid ester polymer (A) is taken as 100 parts by mass (solid content equivalent) are shown in Table 1. Details of the abbreviations and the like shown in Table 1 are as follows. [(Meth)acrylic acid ester polymer (A)] BA: n-butyl acrylate 2EHA: 2-ethylhexyl acrylate 4HBA: 4-hydroxybutyl acrylate PHEA: 2-phenoxyethyl acrylate MA: Methyl acrylate MEA: 2-Methoxyethyl acrylate AA: Acrylic acid HEA: 2-hydroxyethyl acrylate

[0112] [Example 2, Comparative Examples 1 to 3] An adhesive sheet was produced in the same manner as in Example 1, except that the types and ratios of the monomers constituting the (meth)acrylic acid ester polymer (A), the weight average molecular weight (Mw) of the (meth)acrylic acid ester polymer (A), and the amount of crosslinking agent (B) were changed as shown in Table 1.

[0113] [Test Example 1] (Measurement of gel fraction) The adhesive sheets prepared in the examples and comparative examples were cut to a size of 80 mm x 80 mm, the adhesive layer was wrapped in a polyester mesh (product name: Tetron mesh #200), and the mass was measured using a precision balance. The mass of the mesh alone was subtracted to calculate the mass of the adhesive alone. This mass was designated as M1.

[0114] Next, the adhesive wrapped in the polyester mesh was immersed in ethyl acetate at room temperature (23°C) for 24 hours. The adhesive was then removed and air-dried for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50%, and then dried in an oven at 80°C for 12 hours. After drying, the mass was weighed using a precision balance, and the mass of the adhesive alone was calculated by subtracting the mass of the mesh alone. The mass at this time was designated M2. The gel fraction (%) was expressed as (M2 / M1) x 100. The results are shown in Table 2.

[0115] [Test Example 2] (Measurement of storage modulus G') The pressure-sensitive adhesive layers of the pressure-sensitive adhesive sheets prepared in the Examples and Comparative Examples were laminated together to form a laminate having a thickness of 3 mm. A cylindrical body having a diameter of 8 mm (height of 3 mm) was punched out from the resulting laminate of pressure-sensitive adhesive layers to form a sample.

[0116] The storage modulus G' of the above samples was measured under the following conditions by the torsional shear method using a viscoelasticity measuring device (manufactured by Anton Paar, product name "MCR302") in accordance with JIS K7244-1, and the storage modulus G'(-20) at -20°C, the storage modulus G'(25) at 25°C, and the storage modulus G'(85) at 85°C (MPa) were obtained. The results are shown in Table 2. Measurement frequency: 1Hz Measurement temperature: -20℃~150℃

[0117] [Test Example 3] (Measurement of photoelastic coefficient) The adhesive layers of the adhesive sheets prepared in the Examples and Comparative Examples were laminated in multiple layers to obtain a laminate having a thickness of 0.2 mm. The obtained laminate of adhesive layers was cut to 2 cm x 4.5 cm and set in a photoelastic coefficient measuring device (manufactured by JASCO, product name "M-220"). Then, under the conditions below, the phase difference at each tensile load was measured while increasing the tensile load stepwise. Based on the measurement results, the phase difference values ​​at 400 nm, 500 nm, and 600 nm were extracted and plotted, and the photoelastic coefficient (m 2 / N) was calculated. The results are shown in Table 2. Light source lamp: Xe ·Measurement wavelength: 300nm~800nm Slit width: 1 nm

[0118] [Test Example 4] (Measurement of adhesive strength) The light release type release sheet was peeled off from the adhesive sheet obtained in the Examples and Comparative Examples, and the exposed adhesive layer was attached to an easy-adhesion layer of a polyethylene terephthalate (PET) film (manufactured by Toyobo Co., Ltd., product name "PET A4300", thickness: 100 μm) having an easy-adhesion layer, to obtain a laminate of heavy release type release sheet / adhesive layer / PET film. The obtained laminate was cut into a width of 25 mm and a length of 110 mm.

[0119] On the other hand, the following two types of adherends were prepared. (1) Soda lime glass plate (manufactured by Nippon Sheet Glass Co., Ltd., product name "Soda lime glass", thickness: 1.1 mm) (2) A laminate (the polyimide film side is the adherend side) in which a polyimide film with an adhesive layer (manufactured by Toray DuPont, product name "Kapton 100PI", polyimide film thickness: 25 μm, adhesive layer thickness: 5 μm) is attached to one side of a soda-lime glass plate (manufactured by Nippon Sheet Glass Co., Ltd., product name "Soda-lime Glass", thickness: 1.1 mm)

[0120] The heavy release type release sheet was peeled off from the laminate under an environment of 23°C and 50% RH, and the exposed adhesive layer was attached to each of the above-mentioned adherends, and pressurized for 20 minutes at 0.5 MPa and 50°C in an autoclave manufactured by Kurihara Seisakusho Co., Ltd. After that, the laminate was left for 24 hours under conditions of 23°C and 50% RH, and then the adhesive strength (N / 25mm) was measured when the laminate of the PET film and the adhesive layer was peeled off from the adherend using a tensile tester (Tensilon manufactured by Orientec Co., Ltd.) under conditions of a peel speed of 300 mm / min and a peel angle of 180 degrees. The measurement was performed under conditions other than those described here in accordance with JIS Z0237:2009. The results are shown in Table 2.

[0121] [Test Example 5] (Evaluation of peel resistance) In an environment of 23°C and 50% RH, the light release type release sheet was peeled off from the adhesive sheet produced in the examples and comparative examples, and the exposed adhesive layer was attached to one side of a polyimide (PI) film (manufactured by Toray DuPont, product name "Kapton 100PI", thickness: 25 μm, Young's modulus: 3.4 GPa). Next, the heavy release type release sheet was peeled off, and the exposed adhesive layer was attached to the same PI film. Then, after applying pressure of 0.5 MPa and 50°C for 20 minutes in an autoclave manufactured by Kurihara Seisakusho, the laminate was left for 24 hours under conditions of 23°C and 50% RH. The laminate consisting of the PI film / adhesive layer / PI film thus obtained was cut into a width of 50 mm and a length of 200 mm, which was used as a sample.

[0122] The obtained sample was held in a bent state between two holding plates (distance between each plate: 4 mm) made of upright glass plates for 24 hours in an environment of -20°C, as shown in Figure 4. After this static bending test, the test piece was visually inspected for peeling at the interface between the adhesive layer and the adherend at the bent portion. The results are shown in Table 2. ○: No peeling △: Partial peeling (air bubbles) ×: Peeling occurred

[0123] [Test Example 6] (Light leakage resistance) Several COP polarizing plates (thickness 60 μm) were prepared, each of which was composed of a triacetyl cellulose (TAC) film (thickness 25 μm), a polyvinyl alcohol (PVA) film polarizer (thickness 12 μm), and a cycloolefin polymer (COP) film (thickness 23 μm) laminated in that order.

[0124] The light release type release sheet was peeled off from the adhesive sheet produced in the examples and comparative examples, and the exposed adhesive layer was attached to the TAC film side of one COP polarizer. Next, the heavy release type release sheet was peeled off, and the exposed adhesive layer was attached to the COP film side of another COP polarizer in a cross-nicol state. Then, it was pressurized at 0.5 MPa and 50°C for 20 minutes in an autoclave manufactured by Kurihara Seisakusho Co., Ltd., and then left for 24 hours under conditions of 23°C and 50% RH. The laminate consisting of the COP polarizer / adhesive layer / COP polarizer obtained in this way was cut into a width of 50 mm and a length of 200 mm, which was used as a sample.

[0125] The obtained sample was repeatedly bent under the following conditions using a durability tester (manufactured by Yuasa System Co., Ltd., product name "Planar body unloaded U-shaped expansion and contraction tester, model: CL09-typeD01-FSC90"). The bent state was then released and left for 24 hours in an environment of 23°C and 50% RH. Light leakage was then visually confirmed in a dark room using transmitted light from a fluorescent lamp, and light leakage resistance was evaluated according to the following criteria. The results are shown in Table 2. Note that the adhesive sheet of Comparative Example 2 was not evaluated for peel resistance, as it was poorly evaluated.

[0126] <Test conditions> Bending direction: Bending so that the TAC film of one COP polarizer is on the outside and the COP film of the other COP polarizer is on the inside. Minimum bending diameter: 3mmφ Number of flexes: 100,000 Test temperature: 23℃ <Evaluation criteria for resistance to light leakage> No light leakage was observed at the bend. ◯: A very slight amount of light leakage occurred at the bent portion, but was at a level that did not cause any practical problems. ×: Clear light leakage was observed at the bent portion.

[0127] [Test Example 7] (Evaluation of visibility) The light release type release sheet was peeled off from the adhesive sheet produced in the examples and comparative examples, and the exposed adhesive layer was attached to the TAC film side of the same COP polarizer as in Test Example 6. Next, the heavy release type release sheet was peeled off, and the exposed adhesive layer was attached to a retardation film (λ / 4, thickness 25 μm) to obtain a laminate. On the other hand, the light release type release sheet was peeled off from another adhesive sheet produced in the examples and comparative examples, and the exposed adhesive layer was attached to the aluminum layer of an aluminum film reflector formed by vapor-depositing an aluminum layer (thickness 1 μm) on a PET film (thickness 50 μm). Next, the heavy release type release sheet was peeled off, and the exposed adhesive layer was attached to the retardation film of the laminate. Then, it was pressurized at 0.5 MPa and 50° C. for 20 minutes in an autoclave manufactured by Kurihara Seisakusho Co., Ltd., and then left for 24 hours under conditions of 23° C. and 50% RH. The thus obtained laminate consisting of COP polarizing plate / adhesive layer / retardation film / adhesive layer / aluminum film reflector was cut into a piece having a width of 50 mm and a length of 200 mm, which was used as a sample.

[0128] Using a durability testing machine (manufactured by Yuasa System Co., Ltd., product name "Planar body unloaded U-shaped expansion and contraction testing machine, model: CL09-typeD01-FSC90"), the above sample was subjected to static bending for 24 hours under the following conditions. After that, the bent state was released, and the state of reflected light was visually confirmed under fluorescent lighting, and visibility was evaluated according to the following criteria. The results are shown in Table 2.

[0129] <Test conditions> Bending direction: Bending so that the COP polarizer is on the outside and the aluminum film reflector is on the inside Minimum bending diameter: 3mmφ Test temperature: 23℃ <Visibility evaluation criteria> ◯: There was no reflected light at the bent portion, and no decrease in visibility was observed. ×: Unevenness due to reflected light was observed in the bent portion, and a decrease in visibility was observed.

[0130] [Table 1]

[0131] [Table 2]

[0132] As can be seen from Table 2, when the adhesive layer of the adhesive sheet of the embodiment is laminated with two flexible members (polyimide film / polyimide film) and placed in a bent state, no peeling occurs at the interface between the adhesive layer and the flexible member, and the adhesive layer has excellent peel resistance. This effect is fully exhibited in a low temperature environment of -20°C. In addition, the adhesive layer of the adhesive sheet of the embodiment has excellent light leakage resistance and visibility after bending. [Industrial Applicability]

[0133] The present invention is suitable for bonding one flexible member (particularly a polyimide film or a laminate containing a polyimide film) and another flexible member that constitute a repeatedly flexing device. [Explanation of symbols]

[0134] 1...Adhesive sheet 11...Adhesive layer 12a, 12b...Release sheet 2…Repeatedly bent laminated member 21...First flexible member 22...Second flexible member 3. Repeated bending device 31…Cover film 32...First adhesive layer 33...Polarizing film 34...Second adhesive layer 35...Touch sensor film 36...Third adhesive layer 37...Organic EL element 38...Fourth adhesive layer 39...TFT substrate S: Test piece P…Retaining plate

Claims

1. A flexible member and another flexible member that constitute a device that is repeatedly bent; a pressure-sensitive adhesive layer that bonds the first flexible member and the second flexible member to each other; A repeatedly bent laminated member comprising: the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a storage modulus G'(-20) at -20°C and a measurement frequency of 1 Hz of 0.01 MPa or more and 0.20 MPa or less; the absolute value of the photoelastic coefficient of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer at 23° C. and a measurement wavelength of 400 nm is 9.9×10 −10 m 2 / N or less; the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is a pressure-sensitive adhesive obtained by crosslinking a pressure-sensitive adhesive composition containing a (meth)acrylic acid ester polymer (A) and a crosslinking agent (B); The (meth)acrylic acid ester polymer (A) contains, as a monomer unit constituting the polymer, 0.1 mass % or more and 9 mass % or less of an aromatic ring-containing monomer. A repeatedly bent laminated member characterized by:

2. A flexible member and another flexible member that constitute a device that is repeatedly bent; a pressure-sensitive adhesive layer that bonds the first flexible member and the second flexible member to each other; A repeatedly bent laminated member comprising: the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a storage modulus G'(-20) at -20°C and a measurement frequency of 1 Hz of 0.01 MPa or more and 0.20 MPa or less; The absolute value of the photoelastic coefficient of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer at 23° C. and a measurement wavelength of 400 nm is 9.9×10 -10 m 2 / N or less, the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is a pressure-sensitive adhesive obtained by crosslinking a pressure-sensitive adhesive composition containing a (meth)acrylic acid ester polymer (A) and a crosslinking agent (B); The (meth)acrylic acid ester polymer (A) contains, as a monomer unit constituting the polymer, 0.1 mass% or more and 30 mass% or less of an aromatic ring-containing monomer, the gel fraction of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is 30% or more and 80% or less; The adhesive strength of the adhesive layer to soda lime glass is 8 N / 25 mm or more. A repeatedly bent laminated member characterized by:

3. The absolute value of the photoelastic coefficient of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer at 23° C. and a measurement wavelength of 500 nm is 9.9×10 -10 m 2 3. The repeatedly bent laminated member according to claim 1, wherein the bending moment is 0.1 to 1.0 times the bending moment of the laminated member.

4. The absolute value of the photoelastic coefficient of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer at 23° C. and a measurement wavelength of 600 nm is 9.9×10 -10 m 2 The repeatedly bent laminated member according to any one of claims 1 to 3, characterized in that the bending moment is 1 / N or less.

5. The pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a storage modulus G '(85) at 85 ° C. and a measurement frequency of 1 Hz of 0.005 MPa or more and 0.2 MPa or less.

6. The pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer has a storage modulus G '(25) at 25 ° C. and a measurement frequency of 1 Hz of 0.01 MPa or more and 0.2 MPa or less.

7. The repeatedly bent laminated member according to any one of claims 1 to 6, characterized in that the gel fraction of the pressure-sensitive adhesive constituting the pressure-sensitive adhesive layer is 30% or more and 95% or less.

8. A repeatedly flexed device comprising the repeatedly flexed laminate member according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Vacuum filming apparatus

    JP1986015975A

  • Adhesive composition for optical film and adhesive sheet, and optical member using the same

    JP2007138056A

  • Adhesive composition for optical use and adhesive sheet

    JP2007169329A

  • Acrylate-based pressure-sensitive adhesive, and polarizing plate and liquid crystal display device obtained using the same

    JP2008144125A

  • Double coated self-adhesive tape and image display module

    JP2009227826A